2018
DOI: 10.1111/disa.12304
|View full text |Cite
|
Sign up to set email alerts
|

Bringing rights into resilience: revealing complexities of climate risks and social conflict

Abstract: Marginalisation and exclusion are expressed in social conflict and are determinative in distributing risk and resilience. This paper builds on recent literature that has adopted a human rights lens to explore how resilience practice can better account for issues of equity and power. Using the illustrative case of Timor-Leste, it presents an analysis of how human rights principles play out in the settings in which rights are given meaning. The approach reveals the reproduction of patterns of conflict and risk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 80 publications
0
13
0
1
Order By: Relevance
“…DARS conceptualises disaster resilience at the individual level as not solely consisting of personal characteristics or traits, but rather as a process that takes into account broader person-environment resources. DARS items extend beyond personality or individual characteristics to include an assessment of an individual's ecology, such as material resources, social equity, and inclusion (Ensor, Forrester, and Matin, 2018). For instance, DARS items capture material circumstance, such as 'I have enough food to eat', 'I have money to pay my rent or mortgage when it is due', 'I have access to reliable transportation', and 'I have a safe place to go in the event of a disaster'.…”
Section: Strengths and Contributions Of Darsmentioning
confidence: 99%
See 1 more Smart Citation
“…DARS conceptualises disaster resilience at the individual level as not solely consisting of personal characteristics or traits, but rather as a process that takes into account broader person-environment resources. DARS items extend beyond personality or individual characteristics to include an assessment of an individual's ecology, such as material resources, social equity, and inclusion (Ensor, Forrester, and Matin, 2018). For instance, DARS items capture material circumstance, such as 'I have enough food to eat', 'I have money to pay my rent or mortgage when it is due', 'I have access to reliable transportation', and 'I have a safe place to go in the event of a disaster'.…”
Section: Strengths and Contributions Of Darsmentioning
confidence: 99%
“…A number of studies suggest that having economic and physical resources, such as financial stability, food security, and shelter, is associated with positive outcomes and resilience among individuals across multiple types of disaster (Sawada and Shimizutani, 2008; Hobfoll et al, 2009; Ensor, Forrester, and Matin, 2018; Ferreira, Buttell, and Elmhurst, 2018; Beauchamp et al, 2019; Ulrichs, Slater, and Costella, 2019). For instance, in a review of the disaster literature, Norris, Friedman, and Watson (2002) found that having less economic and physical resources consistently predicted more post‐disaster distress.…”
Section: Individual Disaster Resilience Capacitiesmentioning
confidence: 99%
“…Such approaches are important in understanding the lived experiences and cross-generational stories of transformation that are revealed slowly, through sustained engagement and built trust between researchers and participants. Creating the space and means for participants to tell their stories, in their own words, requires creative tools and techniques 12 , including drawing on the arts and on visual means of communication 13 , as well as a willingness on the part of the researcher to give over control of the research process and its outcomes 14 . This approach should be founded on strong intersectionality 15 that recognizes the individual nature of experiences and knowledges, and an openness to diverse (non-western) epistemologies and expressions of knowledge and ways of knowing.…”
Section: Transformation and Justice As Ethics Of Researchmentioning
confidence: 99%
“…The diversity among smallholder farmers draws attention to existing inequalities that relate to vulnerability and shape power, agency, ownership and control of resources, decision-making, and participation within farming systems (Ensor et al 2018). This magnifies the need for resilience-building in CSA to pay attention to the skewed landscape within which CSA adoption decisions have to be made by different farmers.…”
Section: The Concept Of Csa In a Drr Contextmentioning
confidence: 99%